1974
DOI: 10.4315/0022-2747-37.3.119
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Indian Milk Products1

Abstract: A total of 245 samples of Indian milk products comprising khoa, burfi, and pera were examined for chemical, microbiological, and organoleptic qualities, and samples were graded as ‘good,’ ‘fair,' and ‘poor'. The chemical composition of these products varied considerably. Higher bacterial and fungal counts were noted in khoa, as compared to burfi and pera. A variety of microorganisms such as micrococci, sarcinae, aerobic spore-formers, coliforms, staphylococci, streptococci, and lactobacilli were isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The use of preservatives including potassium sorbate for b o a has been reported by several researchers with conflicting results. Rudreshap pa and De (1971) and Rajorhia and Srinivasan (1979) did not observe any enhanced preservation of khoa; Ghodekar (1974) reported that at refrigeration temperatures the shelf-life of khoa could be extended by more than 14 days with potassium sorbate. When khoa was wrapped in paper impregnated with potassium sorbate and stored under refrigeration, the author reported a shelf-life up to 25-27 days.…”
Section: Discussionmentioning
confidence: 97%
“…The use of preservatives including potassium sorbate for b o a has been reported by several researchers with conflicting results. Rudreshap pa and De (1971) and Rajorhia and Srinivasan (1979) did not observe any enhanced preservation of khoa; Ghodekar (1974) reported that at refrigeration temperatures the shelf-life of khoa could be extended by more than 14 days with potassium sorbate. When khoa was wrapped in paper impregnated with potassium sorbate and stored under refrigeration, the author reported a shelf-life up to 25-27 days.…”
Section: Discussionmentioning
confidence: 97%
“…Our finding correlates with Keerthi et al (2018) and Chawla et al ( 2014) who reported the protein content variation of market samples of doda burfi. Further, Ghodeker et al (1974) also reported that the protein content of market samples burfi and peda varied between 12.1 to 20.3 and 6.3 to 11.8%, respectively…”
Section: Proteinmentioning
confidence: 88%
“…Sharma et al (2012) was observed similar observation for milk cake. Further, Ghodeker et al (1974) reported that variation in sugar content of market samples of burfi and peda.…”
Section: Total Carbohydratementioning
confidence: 99%
“…Wide variations in SPC counts of market samples of plain peda were reported by earlier workers. Ghodekar et al (1974), Kamat and Sulebele (1974), Dwarkanath and Srikanta (1977) and Garg and Mandokhot (1987) reported 2x10 3 -3x10 5 , 6x10 2 -1x10 7 , 7.6x10 2 -5x10 3 and 1.1x10 3 -5.6x10 3 per gm, respectively. The average values for yeast and mould count of Mohanthal samples collected from C-1, C-2, C-3 and C-4 markets were 1.83 ± 0.11, 1.96 ± 0.21, 1.86 ± 0.39 and 1.96 ± 0.22 log(cfu/g), respectively and the range was from 1.60 -2.00, 1.60 -2.30, 1.00 -2.30 and 1.48 -2.26 log(cfu/g), respectively.…”
Section: Microbiological Quality Of Mohanthalmentioning
confidence: 94%